The role of economic policy in climate change adaptation - Kai A. Konrad; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper assesses the role of the public sector in adaptation to climate change. We first offer a definition and categorisation of climate change adaptation. We then consider the primary economic principles that can guide the assignment of adaptation tasks to either the private or the public sector, as well as those guiding assignment within the public sector itself. We find that the role of the state in adaptation policy is limited. We identify information policy, the provision of a suitable regulatory framework in some markets, the formation of human capital and policies that foster economic growth and technological and medical knowledge as the main areas in which the public sector has a role in climate change adaptation.
Keywords: H54; Q54; Q58; 330; climate change; adaptation; Schelling conjecture; subsidiarity; Klimaveränderung; Wirtschaftliche Anpassung; Staatliche Einflussnahme